Development of CTL video media based to strengthen Pancasila character in elementary school - Rinny Sartika; Surya Dharma; Sri Milfayetti (Himpunan Pengembang Kurikulum Indonesia, 2025)
The decline in students’ interest and character development in elementary schools highlights the urgency of designing innovative learning media that integrate value-based education with engaging methods. Video learning media based on Contextual Teaching and Learning (CTL) convey messages through visual and audio elements, enabling students to construct knowledge in a meaningful way while internalizing values. This study aimed to develop CTL-based video learning media to strengthen Pancasila character among grade IV students at SD Negeri 104282 Batu Lokong. The research adopted Thiagarajan’s 4D model, which consists of stages: Define, Design, Develop, and Disseminate. The feasibility of the developed media was validated by material, media, and language experts, all categorized as very feasible. Practicality testing with classroom teachers showed that the media was very practical. Effectiveness testing using N-Gain analysis indicated high and moderate improvement levels in strengthening students’ Pancasila character, supported by reliable results. These findings confirm that CTL-based video learning media is feasible, practical, and effective in fostering Pancasila character in elementary students. It is therefore recommended that schools adopt this media as an alternative resource to integrate character education with meaningful learning. Future studies may extend its application to other subjects or different educational levels to further explore its potential impact. Abstrak Menurunnya minat dan pengembangan karakter siswa di sekolah dasar menyoroti urgensi merancang media pembelajaran inovatif yang mengintegrasikan pendidikan berbasis nilai dengan metode yang menarik. Media pembelajaran video berbasis Contextual Teaching and Learning (CTL) menyampaikan pesan melalui elemen visual dan audio, yang memungkinkan siswa membangun pengetahuan secara bermakna sambil menginternalisasi nilai-nilai. Penelitian ini bertujuan untuk mengembangkan media pembelajaran video berbasis CTL untuk memperkuat karakter Pancasila pada siswa kelas IV di SD Negeri 104282 Batu Lokong. Penelitian ini mengadopsi model 4D Thiagarajan, yang terdiri dari tahapan Define, Design, Develop, dan Disseminate. Kelayakan media yang dikembangkan divalidasi oleh ahli materi, ahli media, dan ahli bahasa, semuanya dikategorikan sangat layak. Uji praktikalitas dengan guru kelas menunjukkan bahwa media sangat praktis. Uji efektivitas menggunakan analisis N-Gain menunjukkan tingkat peningkatan yang tinggi dan sedang dalam memperkuat karakter Pancasila siswa, didukung oleh hasil yang reliabel. Temuan ini menegaskan bahwa media pembelajaran video berbasis CTL layak, praktis, dan efektif dalam menumbuhkan karakter Pancasila pada siswa sekolah dasar. Oleh karena itu, disarankan agar sekolah mengadopsi media ini sebagai sumber daya alternatif untuk mengintegrasikan pendidikan karakter dengan pembelajaran yang bermakna. Penelitian selanjutnya dapat memperluas penerapannya ke mata pelajaran lain atau jenjang pendidikan yang berbeda untuk lebih mengeksplorasi potensi dampaknya. Kata Kunci: contextual teaching learning; CTL; media video; sekolah dasar